Clean Cooking and the Rice Cooker Programme: An Evaluation and Policy Perspective - Suntoro, Dedi; Nugroho, Wahid Pinto; Darmaji; Hadiyanto, Fuad; Priyono; Farandy, Alan Ray; Zainuddin, Hazan Azhari; Hesty, Nurry Widya; Sinaga, Paber; Norhadi, Lutfi; Sriyanto, Nanto (Indonesian Journal of Energy, 2025)
Clean cooking is a critical agenda for enhancing access to clean energy in developing nations. In 2023–2024, the Indonesian government implemented a programme to distribute free rice cookers to underprivileged communities, yet this initiative has not previously been evaluated. This study addresses that gap by examining the impact of the rice cooker distribution on household energy consumption and LPG dependency. While several studies have assessed clean cooking programmes—such as biogas, induction, solar-powered stoves, and electric pressure cookers—this research is among the first to evaluate a rice cooker programme in a large-scale field setting, thereby offering novel insights and contributing to the literature on the clean energy transition. A Slovin sampling strategy selected 600 respondents from among 342,621 households across 36 provinces with a margin of error of approximately 4.1%. Primary data were analysed using descriptive statistics, including frequency distributions and cross-tabulations, alongside inferential methods such as ordered logistic regression to investigate the determinants of satisfaction of this program and also t-tests to compare electricity consumption and LPG usage before and after receiving the rice cooker. In addition, secondary data comprising 5,814,476 records on monthly electricity consumption from January 2023 to May 2024 were utilised. Our evaluation reveals that the free rice cooker programme has led to a significant increase in per capita electricity consumption and a corresponding reduction in LPG consumption and subsidies. Although household electricity bills have risen, most respondents report that the efficiency and convenience of the rice cooker offset these additional costs. These findings support the further expansion and continual evaluation of such clean cooking initiatives, enhancing energy resilience in Indonesia and other developing countries.